BEBERAPA TEKNIK ANALISIS DALAM PENELITIAN DAN PENGKAJIAN TEKNOLOGI PERTANIAN - Ketut Sadra Swastika, Dewa (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2004)
Agricultural commodities should be produced efficiently. Otherwise, our agricultural products will not becompetitive with those of other countries, both in international and domestic markets. Efficient farming is possiblethrough adoption of improved technology. The Assessment Institutes of Agricultural Technology (AIATs) in eachprovince are the regional units of the Indonesian Agency for Agricultural Research and Development (IAARD) givena mandate to provide local farmers with an appropriate technology in their respective regions. To meet their mandate,AIATs conduct activities of research and assessments on local specific agricultural technologies based on bio-physicaland socio-economic circumstances of the farmers. Before transferring the technology to the farmers, all technologiesshould be first evaluated in terms of their technical and financial feasibilities using the appropriate tools of analyses.This article offers some techniques of analyses to be used by researchers at the AIATs. Those techniques are PartialBudget analysis, Gains and Losses of technological change, Long Term Investment Analysis, Linear Programming,Regression, and Correlation.Key words : techniques of analyses, efficiency, feasibility, technologyÂ Aspek efisiensi usahatani merupakan pertimbangan utama dalam pengembangan suatu komoditas pertanian,karena di era globalisasi hanya produk yang dihasilkan secara efisien yang dapat bersaing di pasar bebas. Usahataniyang efisien hanya dapat dihasilkan melalui penerapan teknologi tepat guna. Balai Pengkajian Teknologi Pertanian(BPTP) merupakan unit Badan Litbang di daerah yang bertugas menyediakan teknologi tepat guna bagi petani.Sebelum dikembangkan di tingkat petani, semua teknologi yang dikaji harus dievaluasi kelayakan teknis danfinansialnya. Tulisan ini menyajikan beberapa tehnik analisis dari yang sederhana sampai agak kompleks. Tehniktehnikyang disajikan adalah Analisis Anggaran Parsial, Analisis Evaluasi Perubahan Teknologi, Analisis KelayakanInvestasi Jangka Panjang, Analisis Linear Programing (LP), serta Analisis Regresi dan Korelasi. Melalui tulisan ini,diharapkan peneliti di BPTP dapat memanfaatkan tehnik-tehnik analisis ini untuk mengevaluasi kelayakan teknologiyang dikaji, sebelum dikembangkan pada tingkat usahatani yang lebih luas.Kata kunci : teknik analisis, efisiensi, kelayakan, teknologi